Exploring gendered practices by social position in epidemiology: the gender score applied to Germany. (20th October 2021) - Wandschneider, L; Sauzet, O; Razum, O; Miani, C
Abstract: Background: Gender as a relational concept is rarely taken into account in epidemiology, yet an in-depth reflection on gender conceptualisation and operationalisation can advance gender analysis in quantitative health research, allowing for more valid evidence to support public health interventions. We constructed a context-specific gender score to assess how its discriminatory power differed in sub-groups defined by social positions investigated in intersectional analyses, i.e. sex/gender, race, class, age and sexual orientation. Methods: We created a gender score based on gendered social practices on a masculinity-femininity continuum (ranging from 0-1) using data of the German Socioeconomic Panel. With density plots, we exploratively compared distributions of gendered social practices and their variation across social groups. Results: We included 13 gender-related variables to define a gender score in our sample (n = 20, 767). Variables on family and household structures presented with the highest weight for the gender score. Calculating tertiles, the score ranged between 0.01 and 0.68, 0.69 and 0.93 and 0.94 to 1 in women and 0 and 0.18, 0.19 and 0.40 and 0.41 to 1 in men, showing that the distribution for women is more skewed than for men. Comparing social groups, we saw that young individuals, those without children, not living with a partner or currently living in a same-sex/gender partnership, showed more overlap between feminine/masculine social practices among men and women. Conclusions: Our explorative findings showed that the distribution of gendered social practices differed among social groups, which empirically backed up the theoretical notion of gender being a context-specific construct. Economic participation and household structures remain essential drivers of heterogeneity in practices among women and men in most social positions. Concerted efforts must continue to overcome these gender (in)equalities - which are important determinants of health inequalities. Key messages: Family and household structures are crucial to constructing the gender score, indicating that interpersonal relationships are key determinants of gendered social practices. Including gendered practices in representative health monitoring data could allow for differentiation of biological sex and socially constructed gendered practices that drive health inequalities.